IMPROVEMENT OF MECHANISMS FOR CALCULATION AND COLLECTION OF PROPERTY AND LAND TAXES FROM INDIVIDUALS - Akbarova Nilufar , Nematjonovna (THE INNOVATION ECONOMY, 2025)
This article examines the current state of mechanisms for calculating and collecting property and land taxes from individuals in Uzbekistan and explores ways to improve them. The study analyzes factors affecting the accuracy of tax calculation, the efficiency of tax collection, and the quality of tax services. A mixed-methods approach was employed, combining qualitative analysis (of regulatory documents) and quantitative analysis (of tax collection statistics for 2020–2024). Findings highlight the positive impact of digitalization on tax calculation but identify challenges such as incomplete cadastral data, insufficient qualifications of tax officials, and low legal awareness among taxpayers. The article provides practical recommendations for modernizing the tax system